Changes in emotional distress among Ontario education workers during the COVID-19 pandemic: 2021–2023 - Iris Gutmanis; Brenda L. Coleman; Kelly Ramsay; Robert Maunder; Susan J. Bondy; Kailey Fischer; Veronica Zhu; Allison McGeer (PLoS ONE, 2025)
Introduction Education workers experienced increased stress during the COVID-19 pandemic adapting to changing work locations, workload, and pedagogical approaches as well as dealing with pandemic-induced personal life stress. Methods The goal of this Canadian prospective cohort study was to determine whether levels of distress, as measured by the Kessler Psychological Distress Scale (K10), varied significantly over the course of the study (February 18, 2021 to December 22, 2023) among Ontario education workers after adjusting for demographic, work-related, and temporal factors. Exposure data were collected at enrollment and updated annually while vaccination and illness surveys were completed as needed. The K10 was completed periodically throughout the study. Linear mixed effects models were used to assess factors associated with changes in K10 scores. Results On average, K10 scores fell 0.5% every four weeks over the 34-month long study. However, the mean score, that decreased from 23.1 at study start to 19.3 by study end, remained above the cut-off of 15, indicating no ongoing emotional distress. Lower distress scores were also associated with non-winter seasons, older age, being male, and being in very good/excellent health. Alternatively, higher K10 scores were associated with being on medications to reduce anxiety, depression, or sleeping problems, return-to-workplace periods after school lockdowns, and periods of intense non-pharmacological interventions. Conclusion Early identification of people most likely to experience distress is needed so that stress remediation strategies can be quickly implemented. Younger, female education workers with lower rated subjective health, who are taking medications to reduce anxiety, depression, or sleeping problems are likely to be at the highest risk. Recognizing periods that intensify stressful situations, such as pandemics and intervals within them, is important to anticipate the need for assistance.